The mythical pursuit of happiness - a mirage of happiness a brief overview of the philosophy of happiness - Rupčić Kelam, Darija; Kelam, Ivica (2020)
According to some authors, there are several significant projects on the human agenda in the twenty-first century. One of them is the pursuit to find the key to personal happiness. Increasingly, people are beginning to see that systems once created to strengthen a nation, such as the education, the health system, and the welfare system, should serve the happiness and well-being of the individual, not the other way around. Thus, the right to the pursuit of happiness has been transformed into a natural right to happiness. Harari argues that GDP per capita, as a primary measure of national performance assessment, should be supplemented or replaced by GDH – gross domestic happiness. In this paper, we will examine some of the dominant ideologies and strategies aimed at achieving this goal. Optimization of human experience, self deception strategies, and the doctrine of harmony all serve as filters of the reality of the individual. It is necessary to deceive people, to bring them into the state of cheerfulness, to become a cheaper, more productive, and optimal worker in service of capital. The very idea of achieving social harmony is a control mechanism aimed at maintaining balance within the corporate community. Nevertheless, what lies behind the tyranny of unity and the pursuit of happiness is turning into a life that conceals reality and leads to a more profound and further depletion of the range of social, emotional, and personal relationships. Can recognizing a wide range of human emotions, as well as the essential determinants of a human being, such as caring and empathy, help us to live an authentic and happier life?
Po nekim autorima, postoji nekoliko značajnih projekata o ljudskom pitanju u dvadeset i prvom stoljeću. Jedan je od njih potraga za ključem osobne sreće. U porastu je vjerovanje među ljudima da sustavi koji su nekada bili stvoreni da bi osnažili naciju, poput obrazovnog sustava, zdravstvenog sustava i sustava skrbi, trebaju služiti sreći i dobrobiti pojedinca, a ne obratno. Time se pravo na potragu za srećom preoblikovalo u prirodno pravo na sreću. Harari tvrdi da se BDP po glavi stanovnika, kao glavna mjera uspješnosti države, mora dopuniti ili zamijeniti BDS-om – bruto domaćom srećom. U ovom članku ispitat ćemo neke od vodećih ideologija i strategija usmjerenih na postizanje toga cilja. Optimizacija ljudskog iskustva, samo-obmanjujuće strategije i doktrina harmonije služe kao filtri zbilje pojedinca. Važno je zavarati ljude, dovesti ih u stanje radosnosti u kojem bi postali jeftiniji, produktivniji i optimalniji radnici u službi kapitala. Ideja postizanja društvene harmonije upravljački je mehanizam usmjeren na održavanje balansa unutar korporacijske zajednice. Ono što se nalazi iza tiranije jedinstva i potrage za srećom pretvara se u život koji zakriva stvarnost i vodi k dubljoj i daljnjoj potrošnji društvenih, emocionalnih i osobnih veza. Može li nam raspoznavanje širokog spektra ljudskih emocija i bitnih određenja ljudskog bića, poput brige i empatije, pomoći živjeti autentičnijim i sretnijim životom? Pojam sigurnog života, vođen ideologijom sklada i devizom koju Bauman opisuje riječima »ne talasaj«, ideja je života protivnog avanturi, šansi i riziku kao dokazano lažna alternativa životu pobune i žudnje za promjenom mišljenja, a time i žudnje za stvarnom srećom, usuprot iluziji sreće.
Selon certains auteurs, il existe quelques projets importants liés à la question humaine au XXIème siècle. L’un d’entre eux est la quête du bonheur personnel. La croyance selon laquelle les systèmes qui avaient été autrefois créés pour consolider la nation, tels que le système éducatif et le système de santé et de soins, doivent servir le bonheur et le bien-être de l’individu, et non inversement, est en augmentation. De cette manière, le droit à la quête du bonheur s’est transformé en droit naturel au bonheur. Harari affirme que le PIB par habitant, en tant que mesure principale pour quantifier la réussite économique d’un pays, doit être complété ou échangé par le BIB – bonheur intérieur brut. Cet article va questionner certaines des idéologies et stratégies dominantes orientées vers la réalisation de cet objectif. L’optimisation de l’expérience humaine, les stratégies auto-illusoires et la doctrine de l’harmonie servent comme filtres pour la réalité de l’individu. Il est important de tromper les gens, les mettre dans un état de joie, afin qu’ils deviennent de la main d’œuvre bon marché, qu’ils soient plus productifs et produisent des résultats optimaux. L’idée d’acquérir l’harmonie sociale est un mécanisme de gouvernance visant à maintenir l’équilibre au sein des communautés corporatives. Ce qui se trouve derrière la tyrannie de l’unité et la quête du bonheur se transforme en une vie qui masque la réalité et mène à une nouvelle et plus grande consommation des liens sociaux, émotionnels et personnels. L’identification du large spectre des émotions humaines et des déterminations essentielles de l’être humain, telles la considération et l’empathie, peut-elle nous aider à vivre une vie plus authentique et plus heureuse ?
Einigen Autoren zufolge gibt es im einundzwanzigsten Jahrhundert etliche bedeutende Projekte zur Frage des Menschen. Eines davon ist die Suche nach dem Schlüssel zum persönlichen Glück. Unter den Menschen wächst der Glaube, dass Systeme, die einst geschaffen wurden, um eine Nation zu stärken, wie das Bildungssystem, das Gesundheitssystem und das Fürsorgesystem, dem Glück und dem Wohlergehen des Einzelnen dienen sollten und nicht umgekehrt. So wurde das Recht, Glück zu suchen, in ein natürliches Recht auf Glück überführt. Harari stellt die Behauptung auf, dass das Pro-Kopf-BIP als Hauptmaßstab für die Leistungsfähigkeit eines Landes durch das BIG – Bruttoinlandsglück – ergänzt oder ersetzt werden muss. In diesem Artikel werden wir einige der führenden Ideologien und Strategien untersuchen, die dieses Ziel anvisieren. Die Optimierung der menschlichen Erfahrung, selbsttäuschende Strategien und die Doktrin der Harmonie fungieren als Filter der Realität eines Individuums. Es ist wichtig, die Menschen irrezuführen, sie in einen Zustand der Freude zu versetzen, damit sie billigere, produktivere und optimalere Arbeitskräfte im Dienste des Kapitals werden. Die Idee, gesellschaftliche Harmonie zu erreichen, ist ein Lenkmechanismus, der darauf abzielt, das Gleichgewicht innerhalb der korporativen Gemeinschaft aufrechtzuerhalten. Was sich hinter der Tyrannei der Einheit und dem Streben nach Glück befindet, verwandelt sich in ein Leben, das die Realität verschleiert und zu einer tieferen und weiteren Abnutzung sozialer, emotionaler und persönlicher Beziehungen führt. Kann uns das Erkennen eines breiten Spektrums der menschlichen Emotionen und bedeutenden Bestimmungen eines Menschenwesens wie Fürsorge und Empathie helfen, ein authentischeres und glücklicheres Leben zu leben?
Bibliografske bilješke uz tekst.
Abstract ; Sažetak ; Résumé ; Zusammenfassung.
Keywords: Sreća -- Ideologija -- Emocije -- Tiranija -- Iluzija; Badiou, Alain